The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1080/14765284.2014.952515
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese electricity industry: supply capacity and its determinants with reference to OECD countries

Abstract: The paper takes two-stage estimation to investigate the direct and indirect determinants of the capacity of power supply in China, with reference to OECD countries. In the first stage we investigate the determinants of demand for electric consumption and in the second stage we test the impact of demand for consumption on capacity. Our study shows that the direct impact on capacity growth is mainly of GDP growth which is a China-specific effect, and load factor which is a non-China specific effect. Capacity inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Liu et al . () in another study found GDP growth and power prices to influence the capacity of supply in China. In analysing the effect of climate change on energy supply for the Nigerian economy, Akinyemi et al .…”
Section: Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…Liu et al . () in another study found GDP growth and power prices to influence the capacity of supply in China. In analysing the effect of climate change on energy supply for the Nigerian economy, Akinyemi et al .…”
Section: Literature Reviewmentioning
confidence: 91%
“…Since then, researchers have examined energy related issues under broad topics such as energy‐growth nexus (see Adom, ; Kwakwa, ; Kwakwa et al ., ); energy and environmental degradation (see Kwakwa and Aboagye, ; Kwakwa et al, ; Kwakwa and Adu, ); determinants of energy consumption (see Adom and Bekoe, ; Kwakwa et al ., , ); and energy supply (see Adom, ; Kwakwa, ; Liu et al . (). An arguable conclusion one makes from appraising the literature is that these issues have been under researched in developing countries especially those from the African continent.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Te use of coal, natural gas, and nuclear power in electricity generation tends to suppress renewable energy use. Liu et al [37]; in their study on the Chinese energy supply, found that economic growth and energy prices signifcantly impact renewable energy development. Peprah [32] found that electricity supply in sub-Saharan African correlates positively with income, privatization, and labor.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…There are contrasting views on the impact of the changes in prices on the energy market. For instance, Liu, Zhang, and Girardin (2014) argued that a change in the prices for end users does not stimulate electricity generation. On the other hand, Lin and Jiang (2011) found that energy subsidies led to below-supply-cost energy prices for consumers and consequently to low energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Economic growth and the changing structure of the economy have especially increased the demand for electricity, and this has subsequently determined the electricity generation capacity (Liu, Zhang, and Girardin 2014). China is currently the largest consumer of energy as well as the largest greenhouse gas emitter in the world.…”
Section: Introductionmentioning
confidence: 99%